THE EFFECT OF DEBT POLICY, DIVIDEND POLICY, MANAGERIAL OWNERSHIP AND INVESTMENT DECISIONS ON PROFIT MANAGEMENT IN TEXTILE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ricky Andreas Bangun; Nina Purnasari; Valensia; Michella; Rini Herliani (Journal Accounting International Mount Hope, 2024)
The textile industry in Indonesia is one of the backbones of the manufacturing industry. This research is motivated by the aim of analyzingthe influence of debt policy, dividend policy, managerial ownership and investment decisions on earnings management. The research method uses quantitative. The population isThe textile sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023 totaled 22 companies with a sample size of 6 companies and 30 observations. The data collection technique was documentation. The data analysis technique was multiple linear regression analysis using SPSS version 26. The results of the study showed thatDebt Policy and Managerial Ownership have an effect on Earnings Management, Dividend Policy and Investment Decisions do not have an effect on Earnings Management. Simultaneously, it was also found that Debt Policy, Dividend Policy, Managerial Ownership and Investment Decisions do not have an effect on Earnings Management in Textile Subsector Companies Listed on the Indonesia Stock Exchange.